Analisis Uji Tabrak Bodi Mobil Esemka dengan Metode Elemen Hingga - Darmawan, Agus, Agus Dwi Anggono, ST., M.Eng., Ph.D, Dr. Supriyono (2016)
The technology of computing is develop rapidly especially in computer aided engineering software. Most of the human activity has been helped by computer programming. Thus, the computers have became a powerfull tool to design and analysis virtually without the real products or components. The advance technology have become an important resources for any industries to improve the product quality and quantity of production and to survive in the market. The development of computing technology was involved many researchers who develope the finite element software. It was combination between math, engineering and computer. This research was conducted by varying models of collisions. There were front impact, 40% front impact and side impact with a part of frame. Esemka car body was designed by using SolidWorks 2012 software. Then the model is imported into Abaqus 612-1 software with iges format (* .Igs) for crash simulation. From the simulation, it was obtained that the energy absorption can cause deformation in the body structure. It was influenced by the overall structure model of the car, and material thickness. The high deformation of the structure was shown the ability of the structure to absorb the impact energy. It could be occured because the deformation is influenced by energy and strain. The front crash was delivered internal energy as 3,83x1013 Nm, 3,62x1013 Nm for 40% front crash and the side crash give 8,31x1012 Nm.